ASSESSMENT OF JOURNALISM STUDENTS' WRITING PROJECTS COMPLETED INDIVIDUALLY AND IN COLLABORATION - Svitlana Fiialka; Olga Trishchuk; Nadija Figol; Tetiana Faichuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
The authors discuss the issues and benefits of collaborative writing in journalistic education, comparing the texts written by students in different conditions: in group collaboration, individually after prewriting group discussion, and individually without any collaboration. We used a survey for collecting both quantitative and qualitative data. The participants were 21 second year and 15 third-year students, who wrote 18 fiction stories for preschool children (3 were written in the collaborative writing groups of 4, where the students were allowed to choose partners for small groups; 3 in the collaborative writing groups of 4, where the students were not allowed to choose partners; 6 after prewriting group discussion, and 6 without any collaboration). 12 six-year students evaluated delivered texts. We also interviewed 12 teachers of the Department of Publishing and Editing about the collaborative writing tasks at the meeting of the Department. Teachers' interviews were recorded, transcribed and analysed. The students and teachers expressed positive attitudes towards collaborative writing, that contributes to students' learning outcomes and prepare them for teamwork. The highest score got the texts written individually after the prewriting discussion. The stories written by the students who were allowed to choose partners in a group work gained higher scores than texts prepared in randomly created groups. The participants in the self-selected conditions reported that they enjoyed а high level of participation, sharing the workload and supportive behaviour. We also observed the evidences of unequal participation of students in collaboration in small groups where the partners were not familiar. The lowest average score got the texts written with no collaboration. So, we proved that there is a need for implementing prewriting group discussions in the learning process. It is necessary to differentiate the role of each student in collaborative writing to evaluate individual results correctly.